Effect of carbon nanotubes content on the vulcanization kinetic in styrene–butadiene rubber compounds. (6th February 2019) - García, Daniela B.; Mansilla, Marcela A.; Crisnejo, Matías; Farabollini, Hernán; Escobar, Mariano M.
Abstract : Styrene–butadiene rubber compounds reinforced with commercial multiwall carbon nanotubes (MWCNT) in amounts between 0.5 and 10 parts per hundred of rubber (phr) were mixed in a two‐roll mill. A compound with 40 phr of carbon black (CB) was prepared as reference. From rheometric curves at five different temperatures (between 140°C and 180°C), a similar maximum torque and vulcanization time values in the samples reinforced with 10 phr of MWCNT and 40 phr of CB were obtained. The Kamal–Sourour model was used to analyze the influence of the MWCNT content and the vulcanization temperature on the cure rate and induction time. Then, through an Arrhenius plot, it became evident the effect of the reinforcement content on the activation energy of the vulcanization process. Mechanical properties of normalized sheets vulcanized at 160°C indicate that content between 5 and 10 phr of MWCNT are enough to reach a similar performance to that sample with 40 phr of CB. SEM analysis exhibits a good dispersion of MWCNT. Swelling experiments point out a similar absorption degree of toluene in the compounds with 5 phr of MWCNT and 40 phr of CB. POLYM. ENG. SCI., 59:E327–E336, 2019. © 2019 Society of Plastics Engineers